Neutralization of myonecrosis, hemorrhage, and edema induced by Bothrops asper snake venom by homologous and heterologous pre-existing antibodies in mice - Rucavado Romero, Alexandra (1996)
The ability of pre-existing antibodies to neutralize locally-acting toxins of Bothrops asper snake venom was investigated. Hemorrhage, myonecrosis, and edema were markedly reduced in actively immunized mice, although none of these effects was completely abolished. In mice passively immunized with equine antivenom, hemorrhage was prevented completely, while myonecrosis and edema were partially reduced. Pre-existing antibodies did not modify the early stage ( < 3 hr) of venom-induced edema, but significantly accelerated the normalization of this effect within 24 hr. Passive administration of antivenom either 5 or 120 min before venom injection gave similar results, suggesting that the presence of antibodies in the intravascular compartment may fully neutralize locally acting toxins, in this experimental animal model. Overall, the homologous or heterologous origin of antibodies was not a significant factor influencing their in uit,o neutralizing efficiency against local venom effects. Antibody titrations by enzyme-immunoassay using purified toxins and whole venom indicated that serum from actively-immunized mice had a higher proportion of anti-myotoxin antibodies than equine antivenom.